The Use of Personal Metadiscourse over Monologic and Dialogic Modes of Academic Speech. Issue 2 (17th February 2017) - Zare, Javad; Tavakoli, Mansoor
Abstract : This study was an attempt to investigate the functions of personal metadiscursive expressions found in academic monologues and dialogues. The analysis was based on verbal data of 16 academic lectures and discussions. Based on Ädel's (2010) taxonomy of the subtypes and discourse functions of metadiscourse, the two data sets were compared in terms of the use of personal metadiscourse functions. The results show that "references to the audience" metadiscourse was much more prevalent in dialogic speech than in monologic lectures; "metatext" was more frequent in monologues than in dialogues. The findings also suggest that academic lecturers made more frequent use of "discourse organization" metadiscourse expressions in their presentations, because of the presence of a discourse whose topic and phorics management is important. On the other hand, interlocutors used more "audience interaction" metadiscourse expressions in dialogues due to the presence of a direct audience whose active understanding and contribution is vital.